Quality of life in the FOXFIRE, SIRFLOX, and FOXFIRE-Global randomised trials of selective internal radiotherapy for metastatic colorectal cancer - Wolstenholme, J; Fusco, F; Gray, A; Moschandreas, J; Virdee, P; Love, S; Van Hazel, G; Gibbs, P; Wasan, H; Sharma, R (Wiley, 2019)
Selective internal radiotherapy (SIRT) is a liver‐directed treatment involving the injection of yttrium‐90 microspheres into the blood supply of liver tumours. There are very few studies assessing health‐related quality of life (HRQOL) in patients treated with SIRT. Patients with liver metastases from colorectal cancer (CRC) were randomised in the FOXFIRE (FFr; ISRCTN83867919), SIRFLOX (SF; NCT00724503) and FOXFIRE‐Global (FFrG; NCT01721954) trials of first‐line oxaliplatin–fluorouracil (FOLFOX) chemotherapy combined with SIRT versus FOLFOX alone. HRQOL was assessed using the three‐level EQ‐5D, European Organisation for Research and Treatment of Cancer Quality of Life (EORTC QLQ‐C30) and EORTC Colorectal Liver Metastases cancer module (EORTC QLQ‐LMC21) at baseline, ≤3 months, 6 months, 12 months and annually thereafter from randomisation, and at disease progression. Analyses were conducted on an intention‐to‐treat basis. In total, 554 patients were randomised to SIRT + FOLFOX and 549 patients to FOLFOX alone. HRQOL was statistically significant lower in SIRT + FOLFOX patients ≤3 months after SIRT administration in all three instruments, particularly global health, physical and role functioning and symptoms of fatigue, nausea/vomiting and appetite loss. By accepted thresholds, these differences were deemed not clinically important. Differences between SIRT + FOLFOX and FOLFOX alone over the 2‐year follow up and at disease progression were also not clinically important. Although there is some decrease in HRQOL for up to 3 months following SIRT, the addition of SIRT to FOLFOX chemotherapy does not change HRQOL to a clinically important degree in metastatic CRC patients.